Purchase order for supply, installation, testing & commissioning of electrical floor socket with all necessary accessories in the lab for Brac University new campus project - Brac University (Brac University, 2023)
This purchase order has been made between Brac University and Allstar Logistics & Trading for supply, installation, testing & commissioning of electrical floor socket with all necessary accessories in the lab for Brac University new campus project.